Cultural Influence in EFL Learning in Seventh Graders at Colegio la Inmaculada-Chia (2017)
This study is an Action research project that was carried out with seventh graders at Colegio La Inmaculada. The objective of the project was to demonstratehow cultural activities in the classroom influence the learning process of English as a foreign language in the seventh graders at Colegio La Inmaculada. In the development of the research study I designed a didactic unit, based on cultural aspects. Along the development of the research it was possible to clarify the concept of Culture and its influence in the learning process of EFL, taking into account this to develop different activities in the classroom where students´ interests and context are the base to develop a didactic unit and analyze its results. The didactic unit is composed by five lesson plans: 1. Beautiful vacation places in Colombia. 2. Beautiful places in the United States, Mexico, Panamá, and Italy. 3. Native Speaker: Interaction in the classroom. 4. Knowing culture through the meal: United States, Mexico, Panamá and Italy and Colombia. 5. Famous people around the world. According to this, the data was gathered through observations, surveys, interviews and videos. The project shows effectiveness in the activities because they promoted the curiosity of students to know about other cultures, students were motivated to participate in the sessions especially with the native speaker. Additionally, with the present project students are cultural aware of their own cultural aspects and at the same time it promoted the respect for other live stiles.